Dimethyl fumarate effects on paraquat-induced hepatotoxicity in mice via anti-oxidative, anti-inflammatory, and anti-apoptotic activities - Maryam Kavianinia; Hadi Kalantar; Maryam Salehcheh; Layasadat Khorsandi; Saeedeh Shariati; Shokooh Mohtadi; Mohammad Javad Khodayar (Scientific Reports)
Abstract Paraquat (PQ) toxicity is a common problem in the world, associated with oxidative stress, inflammation, and apoptosis. Therefore, the use of agents that reduce these disorders can be effective in the treatment of PQ toxicity. The protective effects of dimethyl fumarate (DMF) on liver disorders have been suggested in many reports. In this study, mice were divided into 6 groups; control, PQ (30 mg/kg, i.p., at day 4), DMF (100 mg/kg, p.o.), and PQ groups pretreated by DMF in three doses 10, 30, and 100 mg/kg, respectively. DMF was administered for 7 days to counteract PQ-induced liver toxicity. On the 8th day, mice were euthanized with ketamine/xylazine, and serum factors, oxidative stress markers, apoptosis index, and inflammatory markers were measured. PQ significantly increased the activity level of serum enzymes, thiobarbituric acid reactive substances, apoptotic factor (Bax/Bcl-2 ratio), inflammatory factors (NF-κB protein expression, tumor necrosis factor-α, interleukin-1β), nitric oxide, and Nrf-2 protein expression. Furthermore, PQ decreased hepatic total thiol and activity levels of catalase, superoxide dismutase, and glutathione peroxidase. However, DMF reduced the harmful effects caused by the imbalance in the oxidant and antioxidant system and histopathological damage in PQ-poisoned mice and improved the damage caused by inflammation and apoptosis.